Globalizing corporate social irresponsibility : a tale of two toxic cities - Benmamoun, Mamoun; Ascencio, Christine; Fisher, James E., active 2024; Kuang, Yunmei (London : NeilsonJournals Publishing, 2024)
La Oroya, Peru, and Herculaneum, Missouri, USA, are two cities 4,000 miles apart but beset with common health and environmental risk: high levels of lead contamination. A key participant in this unfolding tale of environmental disaster has been The Renco Group, a privately held investment holding company based in New York. This case study sheds light on The Renco Group’s Corporate Social Responsibility (CSR) in a developing country (Peru) as distinct from CSR in a developed country (USA) by presenting the distinctive set of formal and informal forces that shape the ethical outcome. The question – one which animates much of this case – is what mechanisms exist that work either collectively or individually to encourage or even require a privately-owned firm to act in a socially responsible manner or, more modestly, to cease activities that are deemed to harm society or the general welfare in a multi-country context?
Description based on XML content.
Keywords: elektronické knihy; electronic books; Social responsibility of business -- Case studies; Globalization -- Case studies; Environmental disasters -- Case studies